2012
DOI: 10.1016/j.mechmat.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Simulated remodeling of loaded collagen networks via strain-dependent enzymatic degradation and constant-rate fiber growth

Abstract: Recent work has demonstrated that enzymatic degradation of collagen fibers exhibits strain-dependent kinetics. Conceptualizing how the strain dependence affects remodeling of collagenous tissues is vital to our understanding of collagen management in native and bioengineered tissues. As a first step towards this goal, the current study puts forward a multiscale model for enzymatic degradation and remodeling of collagen networks for two sample geometries we routinely use in experiments as model tissues. The mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…collagen fibres. The fibres were assigned an initial radius of 50 nm and stiffness of 79 MPa [34]. The fibre volume fraction of the RVEs was 1.2 + 0.07%.…”
Section: Collagen Network and Cell Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…collagen fibres. The fibres were assigned an initial radius of 50 nm and stiffness of 79 MPa [34]. The fibre volume fraction of the RVEs was 1.2 + 0.07%.…”
Section: Collagen Network and Cell Modelsmentioning
confidence: 99%
“…The values of the constants k 1 and k 2 were obtained previously by fitting the experimental data of [32]. Hadi et al [34] found k 1 to be 1.05 Â 10 23 nm s 21 and k 2 to be 0.83. The obtained values are for a specific in vitro case of collagen degradation by bacterial collagenase.…”
Section: Collagen Removalmentioning
confidence: 99%
“…Fibrotic diseases are characterized by excessive scarring due to excessive production and deposition of ECM and disruption of normal healthy protein cross-linking. MMP disrupts collagen cross-linking and increases scarring in cases of excessive collagen concentrations (44,45). We accordingly represent the state of the scar by the equation…”
Section: [12]mentioning
confidence: 99%
“…A strain rate of 100 % strain/min is used ated on the mechanical data of the statically cultured isotropic and anisotropic constructs. The parameter k 3 refers to the degradation rate in absence of strain evaluated by Hadi et al (2012) on the basis of the experiments of Bhole et al (2009). Parameters k 4 and k 5 , describing the collagen degradation, were estimated using the experimental mechanical data of the biaxial isotropic statically loaded constructs and uniaxial cyclically loaded constructs, with strain applied along the scaffold fibers.…”
Section: Scaffold and Collagen Characterizationmentioning
confidence: 99%
“…The degradation of collagen fibers happens according to strain-dependent kinetics. When strain is applied to a collagen gel, the collagen fibers that are oriented in the direction of the strain will degrade slower than the collagen fibers in all the other directions (Bhole et al 2009;Hadi et al 2012).…”
Section: Introductionmentioning
confidence: 99%